# How to prove that sec²θ + csc²θ = sec²θ × csc²θ?

• Difficulty Level : Basic
• Last Updated : 03 Sep, 2021

Trigonometry is a study of the properties of triangles and trigonometric functions. It is used a lot in engineering, science, for building video games, and more. It deals with the relationship between ratios of the sides of a right-angled triangle with its angles. These ratios which are used for the study of this relationship are called Trigonometric ratios. right-angled triangle

### Trigonometric Ratios

There are six basic trigonometric ratios that establish the co-relation between sides of a right triangle with the angle. If θ is  the angle formed between the base and hypotenuse, in a right-angled triangle (as shown in the above figure), then

Attention reader! All those who say programming isn't for kids, just haven't met the right mentors yet. Join the  Demo Class for First Step to Coding Coursespecifically designed for students of class 8 to 12.

The students will get to learn more about the world of programming in these free classes which will definitely help them in making a wise career choice in the future.

sin(θ) = Perpendicular/Hypotenuse

cos(θ) = Base/Hypotenuse

tan(θ) = Perpendicular/Base

The values of the other three function ,that is, cosec(θ), sec(θ), cot(θ) depend on sin(θ), cos(θ), tan(θ) respectively.

cot (θ) = 1/tan (θ) = Base/Perpendicular

sec (θ) = 1/cos (θ) = Hypotenuse/Base

cosec (θ) = 1/sin (θ) = Hypotenuse/Perpendicular

### Trigonometric Identities

A trigonometric equation that holds for every viable value for an input variable on which it is defined is called trigonometric identities. One identity that we are  familiar with is the Pythagorean Identity,

#### Sin2θ + Cos2θ = 1

Divide both sides of the Pythagorean Identity by cosine squared, which is allowed, then,

[cos2θ + sin2θ]/cos2θ = 1/cos2θ

cos2θ/cos2θ + sin2θ/cos2θ = 1/cos2θ

1 + sin2θ/cos2θ = 1/cos2θ

(using the definition tanθ = sinθ/cosθ)

1 + tan2θ = 1/cos2θ

(using the definition secθ = 1/cosθ)

1 + tan2θ = sec2θ

Therefore the next trigonometric identity is,

1 + tan2θ  = sec2θ

Similarly, if divide both sides of the Pythagorean Identity by sine squared then we obtained the last identity,

cot2θ + 1 =  cosec2θ

### How to prove that sec2θ + csc2θ = sec2θ × csc2θ?

Proof:

To solve above problem we require below specified trigonometric identities and ratios :

sec(θ) = 1/cos(θ)  and  cosec(θ) = 1/sin(θ)  ⇢ Eq. 1

sin2θ + cos2θ =1  ⇢ Eq. 2

sec2θ = 1 + tan2θ  ⇢ Eq. 3

cosec2θ  = 1+ cot2θ  ⇢ Eq. 4

There are two ways to solve this problem

1. To prove LHS = RHS using identities

LHS = sec2(θ) + cosec2(θ)

=(1+ tan2θ) + (1+cosec2θ)   (from 3 and 4)

=2 + tan2θ + cosec2θ

RHS= sec2θ × cosec2θ

=(1+tan2θ) × (1+cot2θ)

=2 + tan2θ + cot2θ

Therefore, LHS = RHS.

2. By using trigonometric ratios

LHS= sec2θ + cosec2θ

(from 1), [1/cos2θ ]  +  [1/sin2θ]

=  [sin2θ + cos2θ] / [cos2θ × sin2θ]

(from 2), 1/[cos2θ × sin2θ]

= sec2θ × cosec2θ = RHS

Hence, the given trigonometric equation can be solved in two ways as mentioned above

Therefore, sec2(θ) + cosec2(θ) = sec2(θ) × cosec2(θ).

### Similar Problems

Question 1: Prove, tan4(θ) + tan2(θ) = sec4(θ) – sec2 (θ)   [Hint: take tan2(θ) as common]

Solution:

LHS= tan4θ + tan2θ =  tan2θ (tan2θ + 1)

= (sec2θ – 1) (tan2θ + 1)        {since, tan2θ = sec2θ – 1}

=(sec2θ – 1) sec2θ           {since, tan2θ + 1 = sec2θ}

=sec4(θ) – sec2(θ)  =  RHS

Hence proved.

Question 2: Prove, cos θ / [(1 – tan θ)] + sin θ / [(1 – cot θ)] = sin θ + cos θ

Solution:

LHS =  cos θ / [(1 – tan θ)] + sin θ / [(1 – cot θ)]

=cos θ / [1 – (sin θ/cos θ)] + sin θ/[1 – (cos θ/sin θ)]

= cos θ / [(cos θ – sin θ/cos θ] + sin θ / [(sin θ – cos θ/sin θ)]

= cos2θ/(cos θ – sin θ) + sin2θ/(cos θ – sin θ)

= (cos2θ – sin2θ)/(cos θ – sin θ)

= [(cos θ + sin θ)(cos θ – sin θ)] / (cos θ – sin θ)

= (cos θ + sin θ) =  RHS

Hence proved.

Question 3: Prove, (tan θ + sec θ – 1)/(tan θ – sec θ + 1) = (1 + sin θ) × sec θ

Solution:

LHS = (tan θ + sec θ – 1)/(tan θ – sec θ + 1)

= [(tan θ + sec θ) – (sec2θ – tan2θ)]/(tan θ – sec θ + 1)       [ sec2θ – tan2θ = 1]

= [ (tan θ + sec θ) – (sec θ + tan θ) (sec θ – tan θ)] / (tan θ – sec θ + 1)

= [ (tan θ + sec θ) × (1 – sec θ + tan θ)] / (tan θ – sec θ + 1)

= [(tan θ + sec θ) × (tan θ – sec θ + 1)] / (tan θ – sec θ + 1)

= (tan θ + sec θ)

= (sin θ/cos θ) + (1/cos θ)

= (sin θ + 1) / cos θ

= (1 + sin θ) × secθ  = RHS ; Hence proved.

Question 4: = cosec θ – cot θ     [Hint: Multiply numerator and denominator by (sec θ – 1)]

Solution:

LHS =  (multiply numerator and denominator by (sec θ – 1)) =√[(sec θ -1)2 / tan2θ ]           {sec2θ = 1 + tan2θ ⇢ sec2θ – 1 = tan2θ}

= (sec θ – 1) / tan θ

= (sec θ/tan θ) – (1/tan θ)

= [(1/cos θ) / (sin θ/cos θ)] – cot θ

= [(1/cos θ) × (cos θ/sin θ)] – cot θ

= (1/sin θ) – cot θ

= cosec θ – cot θ = RHS, Hence proved.

Question 5: Prove, (sin θ+cosec θ)2+(cos θ+sec θ)2=7+tan2(θ)+cot2(θ)

Solution:

LHS = {sin2θ + cosec2θ + 2 sinθ cosecθ } + {cos2θ+ sec2θ +2 cosθ secθ}

={sin2θ + cosec2θ + 2} + { cos2θ + sec2θ + 2}

=sin2θ + cos2θ + sec2θ + cosec2θ + 4

=sec2θ + cosec2θ + 5                            [sin2θ +cos2θ = 1]

= (1+ tan2θ) +  (1+ cot2θ) +5              [sec2θ = 1 + tan2θ ;  cosec2θ = 1+ cot2θ ]

=7+ tan2(θ) + cot2(θ) = RHS

Hence proved.

My Personal Notes arrow_drop_up